Influence of Social Circumstances and Health-care Support on Intention-to-quit Tobacco among Population Aged 15–49 Years in India: An Analysis of National Family Health Survey-5 Data - Sinjita Dutta; Ankita Mishra; Vineeta Shukla; Angad Singh; Mausumi Basu; Sonu Goel (Indian Journal of Public Health)
Background: Several national programs targeting a reduction in tobacco use are operational in India, but still the burden is huge. Understanding the influence of social factors and the health-care system on the intention-to-quit (ITQ) tobacco is of immense importance for efforts toward tobacco control and cessation in India. Objectives: To estimate the proportion of the adult population with ITQ tobacco; and to find out if the social circumstances of the study population and the availability of health care support has an influence on their ITQ tobacco. Materials and Methods: Data from India’s National Family and Health Survey (NFHS-5) (2019-2021) were used. The primary outcome was ITQ tobacco among male and female population aged 15–49 years and the explanatory variables were background characteristics, health-care support, and social circumstances. The Statistical Package for the Social Sciences was used for data analysis. Weighted proportion of tobacco users and ITQ tobacco was calculated. Multivariable binary logistic regression was employed to check the association between background characteristics and ITQ tobacco. Results: Overall, 39.6% of the male and 4.1% female participants were tobacco consumers. ITQ was present in 30.1% of male and 31.8% of female tobacco users. Females with high women empowerment were major tobacco users (7.5%). Most participants (40%) who had visited private health facilities had an ITQ. A higher proportion of tobacco use was seen with the presence of another smoker at home. Conclusion: Females had a higher ITQ tobacco compared to males. Visit to a private health facility and the presence of another smoker at home influenced the ITQ.